KONSEP PENDIDIKAN KARAKTER PADA ANAK PERSPEKTIF ISMAIL RAJI AL FARUQI - Edward Gland Tetelepta; Murdianto Murdianto; Liza Husnita; Devin Mahendika; Idris Idris (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
Tawhid is a very important factor in Islam. The thoughts of Ismail Raji Al-Faruqi regarding the principles of the family and also the character of children must of course get a very big influence from Tawhid. Because tawhid is the basic foundation of Islam that must be strong. Tawhid is the core of Islamic teachings that must be the principle and foundation of life. Tawhid, which acts as a principle, has an essence that can underlie every activity of these Muslims. Tawhid means belief and also testimony that there is no God other than Allah. And this is what must be instilled in children so that they have true Islamic characteristics and do not have the thought of shirk by worshiping and taking blessings apart from Allah. Tawhid must be translated into the character of children where the family becomes one of the media that helps to translate this. Moral education and also character development in children must be based on tawhid in accordance with Islamic teachings.